REDUCTION IN CUTS SPEED AT THE BEGINNING OF A SORTING SIDINGS, EQUIPPED WITH QUASI-CONTINUOUS SPEED CONTROL SYSTEM - Nazarov, O. A. (Science and Transport Progress, 2016)
Purpose. Clear and uninterrupted operation of humps depends on the quality of technical equipment and control technology of cuts speed. Technology of interval and purposive regulation of cuts speed is used at most humps. The article discusses ways to reduce the cuts rolling speed to a safe level at the beginning of the sorting sidings equipped with quasi-continuous speed control system. Methodology. It proposed three fundamentally different ways to reduce the cuts rolling speed at the beginning of the sorting siding. The analysis of the ways to reduce cuts rolling speed to a safe level at the beginning of the sorting sidings was conducted using simulation the process of cuts rolling from humps equipped with quasi-continuous speed control. Findings. As a result of analysis, the inappropriateness of opposite elevation using on the roll-out part of the hump after the last separation switch point. Spot regulators of cars speed can be used to reduce the cuts rolling speed at the beginning of the sorting siding, but this leads to a division conditions deterioration on the last separating switch points of long cuts with the following after them short cuts. Reducing the cuts rolling speed at the beginning of the sorting siding can be carried out using the beam on a stationary wagon retarders park brake position. Control Algorithm park brake position is quite simple. All produce should be unhooked from it at a safe speed. If the accuracy of the implementation of the set speed output to unhook from the park brake position is low, it is possible to eliminate the error of point regulators cars speed. Originality. The question where to start location point of wagon retarders zone to reduce speed to cut level requires additional research. Reducing rolling cut the speed at the beginning of the sorting sidings can be carried out using the beam on a stationary wagon retarders park brake position. Practical value. Control Algorithm park brake position is quite simple. All produce should be cut from it at a safe speed. If the accuracy of the implementation of the set speed output to cut from the park brake position is low, it is possible to eliminate the error of point regulators cars speed.